Effect of brushing with conventional versus whitening dentifrices on surface roughness and biofilm formation of dental ceramics - Azevedo, Sarina Maciel Braga [UNESP]; Kantorski, Karla Zanini; Valandro, Luiz Felipe; Bottino, Marco Antonio; Pavanelli, Carlos Augusto [UNESP] (My University, 2012)
The aim of this study was to evaluate the effect of conventional and whitening dentifrices on the weight loss, surface roughness, and early in situ biofilm formation on the surface of dental ceramics. Standardized feldspar ceramic specimens (Vita VM7 and Vita VM13) were submitted to the following experimental conditions: no brushing; brushing without a dentifrice; brushing with a conventional dentifrice; and brushing with a whitening dentifrice. A brushing machine was used to simulate brushing. The mass and surface roughness of all specimens from the test groups were evaluated prior to and after brushing. Ten participants used an oral device for eight hours to evaluate the biofilm formed in situ on the specimens. Scanning electron microscopy was used for qualitative and quantitative analysis of the biofilm. ANOVA and Tukey tests were used to analyze the results of weight loss, surface roughness, and presence of bacteria. A one-way Kruskal-Wallis test was used for bacterial colonization results. For both ceramics, brushing with a whitening dentifrice resulted in weight loss that was significantly greater when compared to brushing without a dentifrice or with a conventional dentifrice. Increased surface roughness was noticed on VM13 ceramic samples with both dentifrices, whereas only conventional dentifrice had a significant effect on the surface roughness of VM7 samples. For both VM7 and VM13, no difference was found between the experimental conditions with regard to the presence or number of bacteria. Cocci and short rods were the predominant microbial morphotypes. Granular or fibrillar acellular material partially covered the specimens. Brushing with a whitening dentifrice resulted in significant weight loss of ceramic restorations, while brushing with both conventional and whitening dentifrices can roughen ceramic surfaces. The increase in roughness was not clinically significant to contribute to increased biofilm formation.
Keywords: aluminum silicate; dental material; potassium derivative; tooth bleaching agent; toothpaste; VITA VM7; biofilm; ceramics; chemistry; clinical trial; comparative study; controlled clinical trial; controlled study; dental porcelain; feldspar; growth, development and aging; human; instrumentation; materials testing; methodology; randomized controlled trial; scanning electron microscopy; surface property; time; tooth brushing; Aluminum Silicates; Biofilms; Ceramics; Dental Materials; Dental Porcelain; Dentifrices; Humans; Materials Testing; Microscopy, Electron, Scanning; Potassium Compounds; Surface Properties; Time Factors; Tooth Bleaching Agents; Toothbrushing